The Influence of Parental Knowledge Level During Pregnancy with Child’s Dental Caries Risk at RSGM-P Nala Husada - Annisa Listya Paramita; Ayulistya Paramita Sutarto; Yongki Hadinata Wijaya (Denta Journal Kedokteran Gigi, 2025)
Background: Awareness and understanding among pregnant women regarding the importance of maintaining oral and dental health play a crucial role in preventing Early Childhood Caries (ECC). Caries risk assessment is an essential part of a comprehensive and age-appropriate patient care approach. This evaluation aims to estimate the likelihood of an increase in caries incidence over time, as well as the potential progression or activity of existing lesions. Objective: to analyze the relationship between parental knowledge during pregnancy about oral and dental health and risk of the dental caries risk in children at RSGM-P Nala Husada. Materials and Methods: This study employed an analytical observational design with a cross-sectional approach. A total of 45 samples were collected from patients at the integration clinic of RSGM-P Nala Husada. Child patients aged 3-5 years were assessed iin dental caries using CAMBRA, while the patient's mother was given a questionnaire to find out what information was known during pregnancy regarding oral and dental health. The Spearman correlation test was chosen because the data used was ordinal. Results: The Spearman correlation test revealed a significant value (p < 0.05) with a strong correlation coefficient (0.666). Conclusion: A strong relationship exists between parental knowledge during pregnancy and the risk of caries in pediatric patients at RSGM-P Nala Husada. Higher levels of maternal knowledge were associated with lower caries risk in children.